Total Lactic Acid Bacteria and Antibacterial Activity in Yoghurt with Addition of Ananas comosus Merr. and Cinnamomum burmannii - Lusia Yotista Enggal Parasthi; Diana Nur Afifah; Choirun Nissa; Binar Panunggal (Amerta Nutrition, 2020)
Background: Diarrhea disease is one of gastrointestinal disorders which is the second leading cause of death in children under five years. Food and beverage contamination is the biggest cause of diarrhea in developing countries. Nanas madu (Ananas comosus Merr.) and cinnamon (Cinnamomum burmannii) have antibacterial properties that can inhibit the growth of Escherichia coli and Salmonella typhi causing diarrhea.Objective: This study aimed to analyze the total differences of Lactic Acid Bacteria (LAB) and antibacterial activity in yoghurt with the addition of nanas madu and cinnamon extract.Methods: This was an experimental study with various treatment in adding honey cream pineapple (0%, 20%, 40%, and 60%) and cinnamon extract (4% and 6%). Total LAB was calculated using the Total Plate Count (TPC) method and antibacterial activity was tested using Kirby Bauer method.Results: There was no significant difference in yoghurt with the addition of honey cream pineapple and cinnamon extract. Yoghurt with the highest LAB was yoghurt with addition 40% of honey cream pineapple and 6% of cinnamon extract (N40M2) with total LAB 1,43 x 1019 CFU/ml. The results of the antibacterial activity showed no significant difference of inhibition zone against S. typhi¸ while there was significant difference of inhibition zone against E. coli. The highest activity against S. typhi was yoghurt with addition 60% of honey cream pineapple and 4% of cinnamon extract (N60M1) resulting 6,81 mm inhibition zone and the highest activity against E. coli was N40M1 resulting 6,77 mm of inhibition zone. Conclusion: Total LAB yoghurt with the addition of nanas madu and cinnamon extract have met FAO and SNI standards with LAB minimum 107 CFU/ml. Antibacterial activity of all yoghurt treatment categorized as medium inhibition (5-10 mm).